Botswana : Skills for Competitiveness and Economic Growth - World Bank (Washington, DC, 2015)
Botswana has pursued prudent macroeconomic policies to manage the revenue streams from diamond exports. It is now an upper-middle-income country that outperforms other countries in Sub-Saharan Africa on key indicators of socioeconomic performance including education, health, and social services. The economic structure in Botswana has undergone changes in recent years, but these changes have not yet ended the countryapos;s reliance on diamond exports. Until recently, Botswana also had a telecommunications monopoly; other utilities are not always accessible at competitive terms. Looking at the lessons offered by successful economies that have grown rapidly in a short period of time, such as those in East Asia, it is clear that export-led industrialization policies contributed to their growth. These policies involve the state taking the lead in crafting and managing market institutions, building physical infrastructure to support industrialization, and minimizing coordination failure within the various segments of the economy. A well-educated and trained population with a wide spectrum of skills also played a vital supporting role in this growth in East Asia. This population had a sufficient skills base to absorb and assimilate technology (via foreign direct investment), operate equipment and infrastructure, and create effective organizations. The country faces significant challenges in transforming its human resources into a force that can drive total factor productivity improvements and, consequently, economic growth.